2017
DOI: 10.20960/nh.620
|View full text |Cite
|
Sign up to set email alerts
|

Excess weight in patients with cystic fibrosis: is it always beneficial?

Abstract: Prevalence of overweight and obese was 6 and 1%. Excess weight status does not offer any benefit in pulmonary function in comparison to normally nourished patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The Australian registry report found that 18% of adults with pancreatic insufficiency experienced “high BMI” compared to 30% of those with pancreatic sufficiency [4] . A number of studies have found higher rates of overweight and obesity among males [7] , [8] , [9] , [16] , while other studies found no sex differences [12] , [14] . Increasing age is associated with rising BMI among the general population and has been found to predict obesity in some CF studies as well [8] , [9] , [14] .…”
Section: Epidemiologymentioning
confidence: 95%
See 1 more Smart Citation
“…The Australian registry report found that 18% of adults with pancreatic insufficiency experienced “high BMI” compared to 30% of those with pancreatic sufficiency [4] . A number of studies have found higher rates of overweight and obesity among males [7] , [8] , [9] , [16] , while other studies found no sex differences [12] , [14] . Increasing age is associated with rising BMI among the general population and has been found to predict obesity in some CF studies as well [8] , [9] , [14] .…”
Section: Epidemiologymentioning
confidence: 95%
“…Rates of overweight and obesity may also vary by country. Single center studies performed between 2007 and 2012 in the US, Greece, and Spain report combined rates of overweight and obesity of 23%, 13.2%, and 7%, respectively [10] , [11] , [12] . With growing recognition of overnutrition in CF, national registries have begun reporting overnutrition statistics.…”
Section: Epidemiologymentioning
confidence: 99%
“…55 Across Europe, the prevalence varies; for example, incidence reports show 13.2% overweight/obese in Greece 56 and 7% in Spain. 57 A recent review illustrated a wide range in obesity prevalence across different settings, but the general consensus is clear, that is, overnutrition is increasing. 58 The cause of this change in nutritional profile (increasing overweight and obesity) is likely to be multifactorial.…”
Section: Changing Nutritional Profilefrom Undernutrition To Overnutri...mentioning
confidence: 99%
“…During the same period, increases in overweight and obesity of between 14.3% and 37% were observed between 2000 and 2020 55 . Across Europe, the prevalence varies; for example, incidence reports show 13.2% overweight/obese in Greece 56 and 7% in Spain 57 . A recent review illustrated a wide range in obesity prevalence across different settings, but the general consensus is clear, that is, overnutrition is increasing 58 …”
Section: Introductionmentioning
confidence: 99%
“…Patients with PS had between 21 and 36 mg/dL more total cholesterol than PI. This is because patients with PI, even with PERT, have fat malabsorption and chronic inflammation [130].…”
Section: Calcium/phosphorus Ratiosmentioning
confidence: 99%